Pengaruh Tingkat Inflasi, Utang Luar Negeri dan Suku Bunga Kredit terhadap Cadangan Devisa Indonesia tahun 1996-2011 - Purnama Putra, Ida Bagus Putu; Indrajaya, I Gusti Bagus (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 2, No. 11, November 2013 (pp. 492-546), 2013)
International trade plays an important role to meet the needs of the country. The international trade, it is necessary foreign exchange.  Foreign exchange saved or commonly known reserves is important for the country mainly used for economic development of a country. This study aimed to determine the effect of simultaneous and partial secarak inflation, foreign debt and interest rates on foreign exchange reserves. The research was conducted in Indonesia by using secondary data. The analysis technique used is regression analysis techniques. Results of data analysis showed simultaneous inflation, foreign debt and lending rates significantly influence the foreign exchange reserves of Indonesia Year 1996-2011, the coefficient of determination (R2) of 0.964 means that 96.4 percent of the variation (rise and fall) Indonesia's foreign reserves in 1996 -2011 influenced by variations (rise and fall) the rate of inflation, foreign debt and interest rates, while the remaining 3.6 percent are influenced by other variables not included in the research model. Partially inflation rate has no effect, external debt and significant positive effect, and lending rates significantly and negatively related to the foreign exchange reserves of Indonesia in 1996-2011.
Keywords: rate of inflation , foreign debt , lending rates , foreign exchange reserves